Nitric oxide and the endothelium : characterisation of in vitro nitric oxide detection techniques and an ex vivo method of measuring endothelial function - Loubser, Dirk Jacobus (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.